The system of the constitution - Vermeule, Adrian, 1968- (New York ; Oxford : Oxford University Press, 2011)
Adrian Vermeule analyses constitutionalism through the lens of systems theory, originally developed in biology, computer science, political science and other disciplines.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Constitutional law -- United States; System theory